Penggunaan Media SAC untuk Meningkatkan Hasil Belajar Menjadi Lebih Baik Atau Meningkat pada Masa Pandemi Covid 19 - Leni Haryani (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The objectives of this Best Practice are 1) To describe the effectiveness of SAC media to improve learning during the Covid 19 Pandemic. 2) To describe learning outcomes using SAC media. Learning is the result of its own construction as a result of its interaction with the learning environment through a process of assimilation or accommodation. Referring to the constructivism paradigm of learning, the principle of SAC media Smart Apps Creator is quite strategic in order to realize effective learning activities. The targets of this best practice activity are students of SMK Muhammadiyah Kalibawang Class XI. The learning steps with SAC media are (1) the initial stage of learning before using the Smart Apps Creator SAC media (2) the learning stage using SAC media during the covid 19 pandemic (3) the assessment stage after learning to use SAC media during the covid 19 pandemic. Experience shows that the learning outcomes of SMK Muhammadiyah Kalibawang students on pressure material, especially learning during the COVID-19 pandemic, are at the KKM completeness score. In order for material learning to run effectively, we innovate the SAC media. The design of SAC media in learning during the COVID-19 pandemic is shown by pictures in the form of photos. This is done so that it is easy to imitate for anyone who wants to develop it. Based on the results of the analysis and discussion, it shows that SAC media in learning during the covid 19 pandemic is effective for carrying out material learning with better learning outcomes.